Two new genera and three new species of freshwater crabs (Crustacea: Pseudothelphusidae: Potamocarcinini) from Chiapas, Mexico - Villalobos, José Luis; Álvarez, Fernando (Zootaxa, 2013)
Two new genera, Sylvathelphusa n. gen. and Tzotzilthelphusa n. gen., and three new species, Sylvathelphusa kalebi n. sp., S. cavernicola n. sp. and Tzotzilthelphusa villarosalensis n. sp., of the tribe Potamocarcinini, family Pseudothelphusidae, are described from Chiapas, Mexico. Sylvathelphusa n. gen. is characterized by a male gonopod with the marginal plate between the caudal and mesial surfaces abruptly widening distally and forming a triangular apical projection; and a mesial process as a strong, acute spine forming a 90º angle with respect to the principal axis of the gonopod. Tzotzilthelphusa n. gen. exhibits a male gonopod strongly bent laterally in the distal third, and a mesial surface rounded distally with acute spinules. Sylvathelphusa n. gen. is similar to Potamocarcinus in gonopod morphology, in both straight and with a mesial process developed as strong tooth in a similar shape and position. Tzotzilthelphusa n. gen. is similar to Phrygiopilus in that the gonopods of both genera develop a supra-apical process that is a continuation of the mesial surface. The new taxa come from the Los Altos de Chiapas region and bring the total number of pseudothelphusid genera in Chiapas to 11.